The Impact of Zinc Oxide Nanoparticles on Cytotoxicity, Genotoxicity, and miRNA Expression in Barley (Hordeum vulgare L.) Seedlings - Ilona Plaksenkova; Inese Kokina; Anastasija Petrova; Marija Jermaļonoka; Vjačeslavs Gerbreders; Marina Krasovska (The Scientific World Journal)
Zinc oxide nanoparticles are one of the most commonly engineered nanomaterials and necessarily enter the environment because of the large quantities produced and their widespread application. Understanding the impacts of nanoparticles on plant growth and development is crucial for the assessment of probable environmental risks to food safety and human health, because plants are a fundamental living component of the ecosystem and the most important source in the human food chain. The objective of this study was to examine the impact of different concentrations of zinc oxide nanoparticles on barley Hordeum vulgare L. seed germination, seedling morphology, root cell viability, stress level, genotoxicity, and expression of miRNAs. The results demonstrate that zinc oxide nanoparticles enhance barley seed germination, shoot/root elongation, and H2O2 stress level and decrease root cell viability and genomic template stability and up- and downregulated miRNAs in barley seedlings.